Zoonoses in Veterinary Students: A Systematic Review of the Literature. - Antonio Sánchez; Miranda Prats-van der Ham; Juan Tatay-Dualde; Ana Paterna; Christian de la Fe; Ángel Gómez-Martín; Juan C Corrales; Antonio Contreras (PLoS ONE, 2017)
Veterinary students face diverse potential sources of zoonotic pathogens since the first years of their academic degree. Such sources include different animal species and pathologic materials which are used at university facilities as well as commercial clinics, farms and other external facilities.The present study utilizes a systematic review of the literature to identify zoonoses described in veterinary students.Web of Science and PubMed.Of the 1,254 titles produced by the bibliographic search, 62 were included in this review. Whereas 28 of these articles (45.2%) described individual cases or outbreaks, the remaining 34 (54.8%) reported serological results. The zoonotic etiological agents described were bacteria, in 39 studies (62.9%), parasites, in 12 works (19.4%), virus, in 9 studies (14.5%) and fungi, in 2 (3.2%) of the selected articles. The selected literature included references from 24 different countries and covered the time period of the last 55 years.The fact that common cases of disease or cases of little clinical importance without collective repercussions are not usually published in peer-reviewed journals limits the possibility to reach conclusions from a quantitative point of view. Furthermore, most of the selected works (66.1%) refer to European or North American countries, and thus, the number of cases due to pathogens which could appear more frequently in non-occidental countries might be underestimated.The results of the present systematic review highlight the need of including training in zoonotic diseases since the first years of Veterinary Science degrees, especially focusing on biosecurity measures (hygienic measures and the utilization of the personal protective equipment), as a way of protecting students, and on monitoring programs, so as to adequately advise affected students or students suspicious of enduring zoonoses.